Peran Homepharmacycare pada Pasien Diabetes Mellitus Tipe II Prolanis terhadap Tingkat Kepatuhan dan Keberhasilan Terapi Di BP Sentra Medika Lebaksiu Tegal - Mita Rodiyatun Najiha; Wahyu Utaminingrum; Much Ilham Novalisa Aji Wibowo (Journal of Tropical Pharmacy and Chemistry, 2017)
Diabetes mellitus disease (DM) is chronic diseases due to the increase of glucose concentration in the body. The compliance and successful treatment of diabetes are needed to prevent complications. The patients’ compliance in using the medicine is an important factor of the successful therapy. One of the most comprehensive interventions for DM patients is Home Pharmacy Care. Objective: This study aims to determine the effect of Home Pharmacy Care role in patients with diabetes mellitus in increasing the compliance and successful therapy. Method: This research is pre experimental research conducted at Bp Sentra Medika Clinic and counseling at home respondents in Lebaksiu ,Tegal with using the method of one group pretest posttest design. Purposive sampling method is used in this research and got 35 respondents. Measurements were made using the MMAS-8 (pretest-postest) and pill count instrument to determine the patient's compliance level and the glucotest to measure the success of therapy characterized by blood sugar levels. Statistics test uses Wilcoxon and Mc Nemar to determine the effect of provision of Home Pharmacy Care intervention on compliace and successful therapy level. The results: showed that a total of 20 patients (57%) comliance to MMAS-8 and pill count scores and a total of 20 patients (57%) of successful treatment were achieved based on controlled blood glucose levels. Conslusion: The statistical test showed that there was a significant difference between before and after intervention marked with the value of p value of both tests was 0,000 so that there is an effect of giving Home Pharmacy Care toward the improvement of compliance and successful therapy. Keywords : diabetes mellitus, homepharmacycare, prolanis, compliance and successful therapy level